An Intelligent System to Analyze Thermal Effect of Stabilized Soil Block - M. S., Latha; B. M., Naveen Kumar; K. J., Thyagaraj; G., Praveen; N., Ramya; Ananthayya , M. B. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Masonry units such as burnt clay bricks and stabilised soil bricks are abundantly used for residential or commercial or any infrastructure construction. Clay mineral absorbs water upon wetting. This paper includes the manufacture of stabilised soil brick (SSB) using natural soil and measuring model room temperature built using burnt clay brick (BCB) and stabilised soil brick. The soil was clayey sand of low plasticity. Stabilizer used to make stabilized soil bricks was 7% cement. Results of tests carried on these bricks at 28 days indicate maximum compressive strength, water absorption. The influence of temperature was measured by constructing two model rooms (1.5 m x 1.5 x 1.5 m) of stabilised soil brick and burnt clay brick. Difference in production of SSB and BCB and variation in measured temperature within rooms indicated environment benefits of SSB compared to BCB.A maximum temperature of 33 0C was attained in the BCB model room during post meridiem whereas a temperature of 29 0C by SSB model room. The maximum average value of ambient temperature was 30 0C thus indicating 12.6% decrease in temperature using SSB for construction instead of burnt clay bricks.